Thickness-dependent electrical and optical properties of Ge8Sb2Te11 thin films. (1st February 2017) - Kumar, Sandeep; Thangaraj, R.
ABSTRACT: The amorphous Ge8 Sb2 Te11 thin films with varying thickness are thermally deposited on well-cleaned glass substrate from its polycrystalline bulk. Absence of any sharp peak confirms the amorphous nature of deposited films. Thickness-dependent electrical and optical properties including dc-activation energy, sheet resistivity, optical band gap, band tailing parameter, etc. of Ge8 Sb2 Te11 thin films have been studied. The optical parameters have been calculated from transmission, reflection and absorbance data in the spectral range of 200–1100 nm. It has been found that optical band gap and band tailing parameter decreases with the increase in Ge8 Sb2 Te11 thin films thickness. The dc-activation energy and sheet resistivity decreases while the crystallization temperature of the amorphous Ge8 Sb2 Te11 films increases with the increase in thickness of the films. The decrease of the sheet resistivity has been substantiated quantitatively using the classical size-effect theory. These results have been explained on the basis of rearrangements of defects and disorders in the amorphous chalcogenide system.